ANALISIS PENGARUH FAKTOR FUNDAMENTAL DAN RISIKO SISTEMATIS TERHADAP HARGA SAHAM, STUDI BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2019 - Siagian, Ade Onny; Indra, Natal (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to determine the effect of fundamental factors and systematic risk on stock prices with the object of commercial banks listed on the Indonesia Stock Exchange in 2010-2019. Fundamental factors are measured using DER, EPS, PBV and PER. Meanwhile, systematic risk is measured using stock beta. The results of the study found that the independent variables, namely DER, EPS, PBV, PER and systematic risk have a simultaneous effect on stock prices. Partially, DER has a significant negative effect on stock prices, EPS has a significant positive effect on stock prices, and PBV has a significant positive effect on stock prices. Meanwhile, PER and systematic risk have no effect on stock prices.